GEOGRAPHICAL REFLECTIONS UPON THE NATURE OF COMMONS STARTING FROM THE READING OF “GOVERNING THE COMMONS “ BY ELINOR OSTROM - Mariateresa Gattullo (Bollettino della Società Geografica Italiana)
This paper proposes a geographic review of Elinor Ostrom’s most famous book “Governing the commons. The evolution of Institutions for Collective Actions”. Its goal is to identify what contribution geographical science can give to defining “the possibilities and limits” related to the use of commons. In the governance of commons, space and territory play a strategic role. Sometimes, however, this role is sacrificed to social, economic and political processes.